A Contrastive Analysis on Street names in London and Hanoi / Hoàng Trung Nghĩa; Supervisor Lê Thị Minh Thảo Ph.D - Hoàng, Trung Nghĩa
Research on place names, especially street names, is always an attractive topic for many researchers. Taking the street names of two districts and one area in London and three urban districts of Hanoi as the object of the survey, the thesis has approached and learned about the street names in the cities centre of London and Hanoi, in the present context that there are rare research on place names from a linguistic perspective on a certain area of Hanoi capital. In this thesis, we study street names in London and street names in Hanoi to find out their structural features and semantic features of the street names of both London and Hanoi. The methods used in this study include: Research approach, Data collection, Data analysis .The thesis studies place names as a complete lexical unit (word/phrase), belonging to the lexical vocabulary in language. Place names have the function of naming specific things that exist on the earth's surface, taking on geographical space, helping to distinguish one thing from another. However, the perception of each ethnic group is different, therefore, the place names also have different interpretations and expressions (phonetic shell). The important thing when learning a place name is a matter of its meaning or reason for naming it. This is due to the change in the internal structure of the language and also the influencing factors of the external environment, what we call "compose structure" and "identification method. The comparative comparison between the two street names of the two capitals is to find out the similarities and differences between the street names of the two countries, thereby contributing to the increase of research literature on said street names particular and the place names in general